Collaborative Governance Dalam Pengelolaan Sampah Clean Cities Blue Ocean (CCBO) Kota Ambon - Sohilait, Julleid Florenza; Rengifurwarin, Zainal Abidin; Ufie, Josef A. (Jurnal Ilmiah Global Education, 2024)
The study aims to describe and talks about how a picture of organizational governance dynamics in waste management through the ambonbonic clean citties program (CCBO) in the city of ambonas and the results and benefits. The research method used is a qualitative descriptive study method with a case study approach, which researchers seek to unearth, describing and discussing the research issues presented for a comprehensive and broad understanding of the focus of the problem examined. As for the findings of research's data. a collaborative government implemented between ambon city and USAID_CCBO is a formal (formal) collaboration but its implementation also applies informal approaches to developing the management of the garbage problem in the city of ambon.